Dung beetles of Brazilian pastures and key to genera identification (Coleoptera: Scarabaeidae) - Tissiani, Ana Silvia Oliveira; Vaz-de-Mello, Fernando Zagury; Campelo-Júnior, José Holanda (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to elaborate supporting tools for the correct identification of Scarabaeidae, by an identification key of genera, and a commented list of the species present in Brazilian pastures. A data survey was performed on the specimens deposited in the main Brazilian collection and reported on the recent scientific literature. The distribution of the species was identified in the Brazilian states, based on information on feeding preference, ecological aspects, and potential for faeces removal action. The species were classified according to their importance for pastures, as: high, medium, and low. A key for the identification of the genera and subgenera of Scarabeidae present in the pastures was constructed through the analysis of the external morphology of the species and, when needed, by the analysis of sexual traits. Twenty genera and 76 species of scarab beetles were recorded for Brazilian pasturelands, among which Dichotomius bos, Dichotomius nisus, Trichillum externepunctatum, Ontherus appendiculatus, Onthophagus aff. hirculus, and Digitonthophagus sp. were considered as the most frequent, widely distributed, abundant, and important. The dichotomous key will contribute to the identification of the genera and subgenera of dung beetles (Scarabaeidae: Scarabaeinae) occurring in the Brazilian pastures.